MICROPUBLISHING’S NEW OPPORTUNITY: WORD PROCESSING TO COM CAN WORK IN THE OFFICE OF THE FUTURE - Gordon, Douglas J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF